ANALISIS PENGARUH FAKTOR FUNDAMENTAL DAN PASAR TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Karo-Karo, Anastasia F.; Silalahi, Donalson (UNIKA Santo Thomas, 2015)
This study aimed to analyze the influence Earning Per Share, Return on Equity, Book Value, Growth Company and market factors, namely Capitalization Rate on stock price on manufacturing companies listed in Indonesia Stock Exchange. The object of this research is manufacturing companies listed in Indonesia Stock Exchange 2010-2012 period who actively publish the financial statements in the period of observation. In this study, the data collected is of secondary data is data obtained indirectly from the object of research. Therefore, in this study the data capture technique using the documentation techniques. The procedure of sample selection is purposive sampling and analysis model used is the Multiple regression to test the hypothesis that the t test and F test and also performed classical assumption. The results showed that the Earning Per Share, Return on Equity, Book Value positive and significant effect on stock prices and capitalization rates and a significant negative effect on stock prices. Based on the test results indicate that simultaneous Earning Per Share, Return on Equity, Book Value, Growth companies and capitalization rates affect stock prices. Variations independent variable Earning Per Share, Return on Equity, Book Value, Growth companies and capitalization rate is able to explain the variation in stock prices by 95.64%.